BIODEGRADATION POTENTIAL OF INDIGENOUS FUNGI ISOLATES FROM WASTE ENGINE OIL CONTAMINATED SOIL - Enerijiofi, Kingsley E.; Enitan, Abigeal A. (FUDMA JOURNAL OF SCIENCES, 2025)
The anthropogenic release of waste engine oil in the environment causes environmental and public health risks. This study aimed at determining the biodegradation potentials of indigenous fungi isolates on waste engine oil. Waste engine oil tainted soils were taken from five different automobile workshops in Benin City. They were analysed using standard laboratory methods. Five fungi isolates; Penicillium, Fusarium, Aspergillus, Trichoderma and Geotrichum species were isolated and screened for their potential to use engine oil as carbon source. Penicillium sp., Fusarium sp. and Aspergillus sp. had the highest and were used for the bioremediation studies. The pH, electrical conductivity, total nitrogen, total hydrocarbon content and optical density were recorded for 25 days at 5 days interval with different oil concentrations (10%, 20%, 30%, and 40%) to monitor the process. The results obtained showed that pH and total hydrocarbon content values were decreasing with increasing incubation time. Penicillium sp. gave the highest electrical conductivity value of 501 us/cm at 30% contamination level at day 25 while Fusarium sp. had the lowest, 239 us/cm at 40% contamination level at day 5. The electrical conductivity and optical density values were increasing with increased incubation days.  Penicillium sp. gave the highest increase in the nitrogen content of 0.91mg/l at 30% contamination level. The study showed that Penicillium sp., Fusarium sp. and Aspergillus sp. were able to biodegrade waste engine oil and therefore recommends that they be used to clean up waste engine oil.